Human Leukocyte Antigen-DP in Acute Nonlymphocytic and Acute Lymphoblastic Leukemia (Journal of the College of Basic Education, 2023)
Acute leukemias are characterized by the elonogenic proliferation of haemopoietic progenitor cells arrested in maturation. Clinicalmanifestations are related to the infiltration of the bone marrow and othertissues by the leukemic blasts. Peripheral blood mononuclear cell (PBMC) from luekemic patients(29)ANLL,(36)ALL and from normal donors(55)were typed for HLA-DP specificities using microlymphocytotoxicity assay. Results showed frequencies of DPw alleles in ANLL patients werenot significantly different from controls ,exept that in DPw1 was absent.In contrast ,in ALL,frequencies of DPw2 and DPw5 were significantlyincreased (p<0.05, relative risk (RR) = 1.95 and p<0.01, RR=4.27,respectively. These results ,therefore ,demonstrate both positive negativeassociations between major histocompatibility complex (MHC) geneproducts which are in only very weak linkage with the rest of HLA ,andALL,ANLL patients.The HLD-DP region could thus contain long sought– after genes influencing susceptibility and resistance to leukeemogenesis.